“Se segura que ainda falta muito mais”: o discurso em torno dos 100 primeiros dias e do primeiro ano do governo Bolsonaro em Isso a Globo não mostra - Avila, Edilaine de (2022)
In the context of society in mediatization, marked by the processes of circulation, several discourses emerge and circulate on different digital platforms, making the mapping of their brands a necessary movement for the understanding of social and media phenomena in contemporary times. Based on the concepts of mediatization, based especially on the contributions of Martino (2018), Gomes (2016), Verón (2014; 2004) and Mata (1999); and circulation, based essentially on the ideas of Fausto Neto (2018a) and Braga (2017a; 2017b); and methodologically supported by the semiology of discourses presented by Verón (2004), this study analyzes the framework Isso a Globo Não Mostra (IAGNM) from the following question: what discursive marks build the criticism produced by the IAGNM framework in relation to the government's stance in Jair Bolsonaro? In view of the preliminary observations, attention was paid to the fact that the attraction is structured from several interdiscourses. Based on this, the main objective of this research is to analyze which discursive marks build the criticism produced by the IAGNM framework in relation to the posture of the Jair Bolsonaro government in the editions alluding to the first 100 days and the first year of his government. Regarding the specific objectives, there are: 1) to identify, in both editions, discursive marks related to the posture of the government of Jair Bolsonaro; 2) map information on digital platforms that are related to what is said in these two editions in order to understand the interdiscursivities constructed; 3) to compare, in the two editions, discursive marks of references to the posture of the government of Jair Bolsonaro. From a survey carried out in the 54 editions of IAGNM, two editions were selected that were unique from the historical point of view, as they thematized the first hundred days and the first year of Bolsonaro's government. The selected episodes were described and, concomitantly, with the help of the Google search engine, the cited references were incorporated into the description to help in the construction of meanings. From the descriptions, discursive marks were identified that point to different criticisms of the federal government's stance. To better systematize the analysis, three categories were created: irony, sarcasm and contradictions. With this, it was possible to perceive that the ways of saying point to interdiscursivities of various orders, such as references to sayings from different sources, temporalities and genres (informative, fictional), which refers to the complexity of discourses and semiosis.